Supply chain environmental R&D cooperation and product performance: Exploring the network dynamics of positional embeddedness. Issue 4 (October 2018) - De Stefano, M. Cristina; Montes-Sancho, María J.
Abstract: Companies increasingly need to work with their partners to address sustainability issues, but benefits from environmental R&D cooperation can be limited by the complexity of its management. This paper examines how the interplay between dyadic and network relationships can contribute to increase the success of environmental R&D cooperation. Using secondary data, we examine whether the positional embeddedness in the supply network structure of partners engaged in environmental R&D cooperation amplifies the effects of cooperation on product performance. Non-monotonic effects of environmental R&D cooperation and embeddedness are also tested. The results indicate that the positional embeddedness of partners triggered by multiple sourcing strategy amplifies the effects of environmental R&D cooperation on product environmental performance. The interaction effects become however insignificant in the presence of increasing complexity and excessive environmental R&D cooperation. Highlights: Environmental R&D cooperation has non-monotonic effects on product performance. Positional embeddedness increases the effects of R&D cooperation on performance. Complexity and excessive R&D cooperation are insignificant on performance. Multiple sourcing strategies facilitate innovation development and diffusion. Managers must test supply network structures and balance supplier portfolio.